2016
DOI: 10.15625/1859-3097/16/1/6527
|View full text |Cite
|
Sign up to set email alerts
|

KẾT QUẢ BƯỚC ĐẦU NGHIÊN CỨU TỐC ĐỘ LẮNG ĐỌNG, NGUỒN TRẦM TÍCH ĐÁY VỊNH HẠ LONG: DẤU HIỆU TỪ KHOÁNG VẬT SÉT, ĐỒNG VỊ 210Pb VÀ 137Cs

Abstract: Vịnh Hạ Long là một trong những di sản thiên nhiên thế giới, hàng năm, vịnh thu hút nhiều du khách trong và ngoài nước. Tuy nhiên, trong những năm gần đây, cảnh quan vịnh bị tác động bởi hàng loạt các tác động tiêu cực-bồi lắng đáy vịnh là một trong những tác động tiêu cực lớn. Đáy vịnh Hạ Long bồi cạn ra sao? nguyên nhân nào gây ra? Theo cách tiếp cận từ nguồn cung cấp đến bồn lắng đọng trầm tích "source-to-sink" phối hợp với kết quả thành phần khoáng vật sét cùng đồng vị phóng xạ 210 Pb và 137 Cs, nghiên cứu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…The sediment volume that had to be dredged to maintain a minimum depth of the navigation channels was about 0.78 × 10 6 m 3 in 2013 and 1.17 × 10 6 m 3 in 2015 with a high induced cost (e.g., 6.6 million USD in 2013) [31]. Many studies were recently devoted to find the cause of siltation in the navigation channel deposition and to propose solutions, focusing on geomorphology [32], geology [33], hydrodynamics and sediment transport [34][35][36][37][38]. Lefebvre et al [38] showed in particular that tidal pumping created a net upstream transport of sediments which settled in a near-bed layer at low turbulent energy, causing the silting up of the channels of Hai Phong port, particularly in the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…The sediment volume that had to be dredged to maintain a minimum depth of the navigation channels was about 0.78 × 10 6 m 3 in 2013 and 1.17 × 10 6 m 3 in 2015 with a high induced cost (e.g., 6.6 million USD in 2013) [31]. Many studies were recently devoted to find the cause of siltation in the navigation channel deposition and to propose solutions, focusing on geomorphology [32], geology [33], hydrodynamics and sediment transport [34][35][36][37][38]. Lefebvre et al [38] showed in particular that tidal pumping created a net upstream transport of sediments which settled in a near-bed layer at low turbulent energy, causing the silting up of the channels of Hai Phong port, particularly in the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a fact that open pits coal mining, that was practised in the past, contributed soil from the unstabilized tailings into the Bay (Figure 5). Peninsular coastal Malaysia 0.2-0.42 [44] Brunei Bay, Malaysia 0.47-2.13 [45] Gulf of Ton Kin 0.47-0.75 [21] Central Ha Long Bay 0.45 ± 0.17 much lower than the Redfield Ratio of 106:16:1 characterized for marine phytoplankton. Sediment with C:N:P lower than the Redfield Ratio has also been reported from other tropical river mouths [48,49].…”
Section: Discussion Temporal and Spatial Variation Of Sedimentation Rate In The Ha Long Baymentioning
confidence: 99%
“…Investigating the mineralogy of bottom sediment in Ha Long Bay, Bui Van Vuong, et al [21] have shown that the sediment accumulating in bottom of Ha Long Bay was derived not only from the local soil, but also from soil eroded inland and carried by the Red River and Thai Binh River systems. However, the temporal and spatial variations of sedimentation rate in the Bay were not systematically studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Nguồn từ hệ hống sông Hồng đã giảm đi khá nhiều khi đi vào Vịnh Hạ Long thông qua các kênh Cái Tráp, Lạch Huyện, Hoàng Châu và vòng qua đảo Cát Bà. Từ trước 1990 thành phần khoáng vật sét có nguồn gốc từ sông Hồng khá cao, kể từ sau 1990 thì nguồn cung cấp từ phong hóa bóc mòn các đá xung quanh đi vào Vịnh Hạ Long cao hơn [7]. Ở quần đảo Cát Bà và Vịnh Hạ Long sinh vật có tổng số 4622 loài cả ở trên cạn và dưới nước.…”
Section: Mở đầUunclassified
“…pH trầm tích chịu ảnh hưởng của cả môi trường biển và lục địa và giá trị pH nằm trong ngưỡng của môi trường tự nhiên (6,(5)(6)(7)(8)5), giá trị pH dao động từ 6,96 đến 8,09, trung bình 7,25 (Bảng 2).…”
Section: Ph Và Eh Trầm Tíchunclassified